Exposure to Helicobacter pylori infection in early childhood and the risk of allergic disease and atopic sensitization: a longitudinal birth cohort study. Issue 4 (April 2014) - Amberbir, A.; Medhin, G.; Abegaz, W. E.; Hanlon, C.; Robinson, K.; Fogarty, A.; Britton, J.; Venn, A.; Davey, G.
Summary Background An inverse relation between Helicobacter pylori infection and allergic disease has been reported by a range of independent epidemiological studies, but evidence from longitudinal studies is scarce. Objective We have investigated the effects of H. pylori infection on the incidence and prevalence of allergic diseases and sensitization in a low‐income birth cohort. Methods In 2005/2006, a population‐based birth cohort was established in Butajira, Ethiopia, and the 1006 singleton babies born were followed up at ages 1, 3, and 5. Symptoms of allergic disease were collected using the ISAAC questionnaire, allergen skin tests performed, and stool samples analysed for H. pylori antigen and geohelminths. Multiple logistic regression was used to determine the independent effects of H. pylori measured at age 3 on the incidence of each outcome between ages 3 and 5 years (in those without the outcome at age 3), controlling for potential confounders, and to additionally assess cross‐sectional associations. Results A total of 863 children were followed up to age 5. H. pylori infection was found in 25% of the children at both ages 3 and 5, in 21% at age 5 but not 3, and in 17% at age 3 but not at age 5. H. pylori infection at age 3 was significantly associated with a decreased risk of incident eczema between ages 3 and 5 (adjusted OR, 95% CI, 0.31; 0.10–0.94, P = 0.02). Cross‐sectionally at age 5, H. pylori infection was inversely associated with skin sensitization (adjusted OR, 95% CI, 0.26; 0.07–0.92, P = 0.02). Conclusion and clinical relevance These findings provide further evidence to suggest that early‐life exposure to H. pylori may play a protective role in the development of allergy.